2017
DOI: 10.1371/journal.pntd.0005940
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, actionable diagnosis of urban epidemic leptospirosis using a pathogenic Leptospira lipL32-based real-time PCR assay

Abstract: BackgroundWith a conservatively estimated 1 million cases of leptospirosis worldwide and a 5–10% fatality rate, the rapid diagnosis of leptospirosis leading to effective clinical and public health decision making is of high importance, and yet remains a challenge.MethodologyBased on parallel, population-based studies in two leptospirosis-endemic regions in Brazil, a real-time PCR assay which detects lipL32, a gene specifically present in pathogenic Leptospira, was assessed for the diagnostic effectiveness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
2
29
0
1
Order By: Relevance
“…Increasing patients' delay in seeking care from 1 day to 10 days increased costs threefold, and DALYs sevenfold (S3 Table, S4 Table). This is consistent with recommendations for early diagnosis and treatment in order to avoid worsened health outcomes [34,35]. For patients referred to hospitals on their first or fourth day of illness, we found that PCR-led strategies were more likely to be on the effectiveness frontier compared to RDT-led strategies (Figs 1 and 2, S3 Fig, S4 Fig) since PCR tests had higher accuracy in the early stage of illness where RDTs were more accurate in the later stage (S1 Table).…”
Section: Discussionsupporting
confidence: 85%
“…Increasing patients' delay in seeking care from 1 day to 10 days increased costs threefold, and DALYs sevenfold (S3 Table, S4 Table). This is consistent with recommendations for early diagnosis and treatment in order to avoid worsened health outcomes [34,35]. For patients referred to hospitals on their first or fourth day of illness, we found that PCR-led strategies were more likely to be on the effectiveness frontier compared to RDT-led strategies (Figs 1 and 2, S3 Fig, S4 Fig) since PCR tests had higher accuracy in the early stage of illness where RDTs were more accurate in the later stage (S1 Table).…”
Section: Discussionsupporting
confidence: 85%
“…The accuracy of this test was evident in several studies with a sensitivity of 61%–86% and a specificity of 99%–100%. Both high yield and rapidity of the test make it practical in the diagnosis of severe leptospirosis, which needs prompt treatment, and can avoid unnecessary immunosuppressive drugs during management of treatable DAHs 26–28. Moreover, we found that Leptospira IgM from blood samples was negative in day 1, but turned to positive result later in day 8 (Department of Medical Sciences, Thailand, 2018; sensitivity 92%, specificity 98.7%; compare with microscopic agglutination test).…”
Section: Discussionmentioning
confidence: 92%
“…The studies included were conducted in different countries and were published from 1992 to 2018. Some of the included studies used different methods; thus, the data were reported as separate independent studies [12,[22][23][24][25][26][27][28][29][30][31][32].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%